What Makes an Enterprise Sustainable? or: is „Green“ Really „Green“? - Barbian, Dina (Proceedings of the 5th European Conference on Intellectual Capital, University of the Basque Country, Bilbao, Spain, 11-12 April 2013, 2013)
The main goal of enterprises is to maximize their profits and to minimize their costs. This fact – coming from utilitarianism and the neo-classics – is not new. But by doing this, firms don’t recognize that they cause a huge amount of negative externalities with an extreme impact on the ecosystem. The consequences are a decreasing quality of the environment and natural resources, resulting in social costs (diseases, epidemics, life quality reduction) and ecological costs (degradation of air, water and soil, and ozone depletion). It is evident that every production process has an impact on the environment when it extracts resources from the environmental system and inserts waste into it. The ecosystem has its limits and its own complex rules, based on biochemical, geochemical, physical, oceanographic etc. processes. The environmental system has the unique capacity to assimilate waste and to regenerate. How can enterprises drive their processes in a socially and environmentally friendly manner? How could economic interests balance with social and environmental incentives? The concept of sustainable development can give some answers. Our way of life, which has become “greener” in recent years is a step towards sustainability: we produce “green products”. We use “green IT”. We live in “green homes”. But is that really a sustainable path? Technological progress can help to implement strategies and apply principles for sustainable competitive positioning and long-term success for sustainable enterprises. This paper gives an insight into the complexity of our world system, and the interdependences between enterprises and the natural environment. By applying a simple world model the author tries to develop a concept which is the basis to explain what does sustainability really means. The World Commission on Environment and Development (WCED) contributed the most frequently quoted definition. At the end of this article some “green” examples are shown and strategies for successful sustainable enterprises are developed.
Keywords: sustainable development; environmental system (ecosystem; ecological system); laws of thermodynamics; world model; strategic management